Radiation Dose and Image Quality of Bladder Cancer Patients Analysis on Abdominal CT-Scan Examinations - Anthon, R.; Intifadhah, S. H.; Putri, E. R. (National Research and Innovation Agency, 2025)
The bladder is a subperitoneal, hollow muscular organ that acts as areservoir for urine and located in the lower abdomen. Bladder cancer is one of health issues that can affect many people each year. Bladder cancer ranks as the 10th most common cancer worldwide. Early management includes cancer screening using abdominal CT-Scan. The objective of this study was to analyze the radiation dose received by patients and the image quality of patients underwent abdominal CT scans based on the Signal to Noise Ratio (SNR) and Contrast to Noise Ratio (CNR) values obtained. Data analysis management, specifically using quantitative analysis techniques, involved observing 20 bladder cancer patients with a total of 2,653 images. The IndoseCT software was used for analyzing the radiation dose to patients, while the IndoQCT software was used for analyzing image quality in CT-Abdomen examinations based on Signal to Noise Ratio (SNR) and Contrast to Noise Ratio (CNR) values. The results showed that the radiation dose received by patients during CT-Abdomen examinations was higher than the dose output by the device. The maximum dose output by the device (CTDIvol) was 50.10 mGy, and the minimum was 6.70 mGy, while the maximum dose received by patients (SSDE) was 53.34 mGy, and the minimum was 9.34 mGy. The image quality results for CT-Abdomen examinations based on SNR and CNR values indicated that the image quality obtained was adequate for diagnostic purposes.